Resistensi Marginal: Perlawanan Masyarakat Desa Sampali Terhadap Ekspansi Citraland Megapolitan - Kurniawan, Dimas (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research is entitled "Marginal Resistance: Resistance of the Sampali Village Community to the Citraland Megapolitan Expansion," and aims to examine the forms of resistance carried out by the Sampali Village community against Citraland's megapolitan expansion. Sampali Village, which is located on the outskirts of the city, is facing serious threats to the sustainability of its people's lives due to this large development project. Village residents, the majority of whom work as farmers and laborers, feel the direct impact of land expropriation that threatens their livelihoods and cultural heritage. This research uses qualitative methods with a case study approach to reveal the dynamics of conflict and resistance strategies implemented by local communities. Research findings show that forms of community resistance include protests, filing petitions, and legal efforts to defend land rights. The Sampali Village community showed strong solidarity and courage in facing pressure from developers. In addition, this research highlights the injustices that often arise in the development process where economic interests dominate without considering the welfare of local communities. The case of Sampali Village reflects the importance of inclusiveness and social justice in every development plan to avoid prolonged conflict and wider negative impacts. Thus, this research contributes to the understanding of marginal resistance and provides important insights for more equitable and sustainable development policies.